Influência da razão SiO2/Al2O3 e da acidez em zeólitas tipo ZSM-5 no craqueamento de óleo de soja bruto - Bravo, Carlos Andres Ortiz (2017)
Na-ZSM5-type zeolites with three different SiO2/Al2O3 molar ratio (30, 60 and 90) were synthesized and submitted to three types of post synthesis treatments: 1) saline wash (Na-ZSM5L); 2) Ionic exchange in order to obtain its acid form (H-ZSM5) and 3) Wet impregnation with niobium pentoxide (Nb2O5/Na-ZSM5). Variations of SiO2/Al2O3 molar ratio caused variations in texture properties. Moreover, differences in the SiO2/Al2O3 molar ratio were observed between the synthesis gel and the zeolite obtained. There was a general trend of decrease in the total acidity of the catalyst with the SiO2/Al2O3 ratio increase. However, the relationship between the types of acidity (low, medium or high) varied depending on the zeolite type, that is, whether it was in its sodium, acidic form or impregnated with niobium. For example, for the sodium and niobium impregnated zeolites, were identified low and medium acidity, increasing for the two cases the average acid sites in relation to the low acid sites with the increase in the SiO2/Al2O3 ratio. In relation to H-ZSM5 zeolites, ammonia desorption peak at high temperature, typical of H-ZSM5 zeolite, was identified. This result was very interesting, because it shows the possibility to manipulate the type of acidity according to the type of post synthesis treatment. Organic liquid product was mainly composed by hydrocarbons in the gasoline range and by aromatics. The effect of the SiO2/Al2O3 ratio on the reaction product distribution varied according to the type of zeolite used. In fact, for the sodium-type zeolites and those impregnated with niobium, the increase in the SiO2/Al2O3 ratio caused a decrease in the gasoline yield. In contrast, for H-ZSM5 type zeolites, the highest values of gasoline yield were observed for zeolite H-ZSM5 (90). The H2 effect was especially observed in the decrease in the production of aromatic hydrocarbons and in the increase in water production. This latter result could be related to the amount of coke formed. The increase in SiO2/Al2O3 ratio decreased the amount of coke formed in all the zeolites used. In addition, ion exchange and niobium impregnation treatments caused a decrease for coke formed.